Experience of Working of Mine Fields Districts of Potash Mines with a Longwall Turn in RUE "PA "Belaruskali" - A.D. Smychnik (Механика машин, механизмов и материалов, 2009)
In the article the regularities of interaction of the modern mechanized complexes and the elastic deformed medium of districts of mine fields of potash mines of RUE "PA "Belaruskali" with the small sizes are shown. Offered new schemes of working with a turn of the mechanized complex on the boundary of a panel, preventing rock falls of a roof at driving of the end districts are examined. Possible ways of increase of productivity of the mining equipment are described.